Different methods to determine maximum heart rate and its influence on internal training load in futsal players - Dutra, Yago Medeiros [UNESP]; Silva, Alexsandro Santos da [UNESP]; Júnior, Oswaldo Tadeu da Silva [UNESP]; Penafiel, Matheus Luiz [UNESP]; Munoz, Yacco Volpato [UNESP]; Fraioli, Carlos Gabriel [UNESP]; Moura, Dagnou Pessoa de [UNESP]; Junior, Antônio Carlos Tavares [UNESP]; Dos-Santos, Júlio Wilson [UNESP] (UNESP - Universidade Estadual Paulista, 2024)
Aims: The purpose of this study was to compare maximal heart rate (HRmax) determined in official match (OM), Yo-Yo intermittent recovery test level 1 (YYIR-1), and age-predicted equations in futsal players, also assessing the effects of using these HRmax approaches on internal training load (TL) outcomes since HRmax influences the TL internal calculation. Methods: HRmax of professional male futsal players (n=8) was determined in OM, YYIR-1 and by four age-predicted equations: Fox-HRmax; Hossack-HRmax; Tanaka-HRmax; Nikolaidis-HRmax. Additionally, the internal TL of seven training sessions was calculated individually each day for each of the six HRmax approaches using Edwards's method. Statistical analysis comprised ANOVA for repeated measures (p < 0.05) and Cohen's d effect size (ES). Results: Fox-HRmax overestimated all other HRmax-equations and YYIR-1 HRmax, and Nikolaidis-HRmax overestimated Tanaka-HRmax and Hossack-HRmax (p = 0.01; ηP2 = 0.496). TRIMP statistical results were statistically like HRmax but underestimated (p = 0.008; ηP2 = 0. 513). Pairwise inferences showed that OM HRmax presented a large effect (d: 0.83) in comparison to the YYIR-1 and a moderate effect (d: -0.35 to 0.35) in comparison to the Fox-HRmax, Tanaka-HRmax and Hossack-HRmax. Nikolaidis-HRmax presented a lower difference with OM, HRmax (d: -0.13, trivial) and TRIMP (d: -0.09, trivial). Conclusion: HRmax from OM presented a higher effect in comparison to the YYIR-1, while the Nikolaidis-HRmax equation was lower and differed from OM HRmax. Futsal coaches are encouraged to use OM to determine HRmax and Nikolaidis-HRmax equation when maximal efforts are not possible, avoiding overestimated TRIMP that may impair training load prescription and physical gains.
Keywords: Age-related equations; official match; team sport; training impulse; Yo-Yo intermittent recovery test.